Hidden Markov Models for Zero-Inflated Poisson Counts with an Application to Substance Use - DeSantis, Stacia M. (2011)
Paradigms for substance abuse cue-reactivity research involve short term pharmacological or stressful stimulation designed to elicit stress and craving responses in cocaine-dependent subjects. It is unclear as to whether stress induced from participation in such studies increases drug-seeking behavior. We propose a 2-state Hidden Markov model to model the number of cocaine abuses per week before and after participation in a stress- and cue-reactivity study. The hypothesized latent state corresponds to ‘high’ or ‘low’ use. To account for a preponderance of zeros, we assume a zero-inflated Poisson model for the count data. Transition probabilities depend on the prior week’s state, fixed demographic variables, and time-varying covariates. We adopt a Bayesian approach to model fitting, and use the conditional predictive ordinate statistic to demonstrate that the zero-inflated Poisson hidden Markov model outperforms other models for longitudinal count data.